THE INFLUENCE OF BRAND IMAGE, SOCIAL INFLUENCE, STATUS CONSUMPTION, PRICE QUALITY INFERENCE, AND ATTITUDE TOWARDS THE PURCHASE INTENTION OF COUNTERFEIT ELECRONIC PRODUCTS VIA TIKTOK SHOP IN SEMARANG (A STUDY ON THE PREVALENCE OF COUNTERFEIT PRODUCTS) - Daffa Luqman Raf, Gofita Athallarizq; Cahyaningratri, Cahyaningratri; Hasya, Afina (Diponegoro Journal of Management, 2024)
ABSTRACT The development of technology has made it possible for counterfeiters to make high-quality goods, sell them online to customers throughout the world, and imitate the branding of real products remarkably well. One platform that has emerged as one of the most popular channels for counterfeiters to conduct their operation is TikTok. The platfrom has allowed the activity where online counterfeit sellers can engage with online buyers. To aid the investigation of how brand image, social influence, status consumption, and price quality inference affects the attitudes of Gen Z in Semarang towards counterfeit electronic products, as well as the moderating effect of customer attitude towards counterfeit electronic products towards purchase intention of counterfeit electronic products, the Theory of Planned Behavior was used. The data that were obtained from 178 respondents in Semarang City was analyzed using Partial Least Structures Structural Equation Modeling (PLS-SEM). From the findings in this study, brand image, social influence, and status consumption have a positive relationship towards customer attitude towards counterfeit electronic products as well as a significant one. Price quality inference, however, was found to only have a positive relationship without significance. On top of that, customer attitude towards counterfeit electronic products also has a positive and significant relationship towards purchase intention of counterfeit electronic products. With this in mind, all the hypotheses except one were accepted. Under those circumstances, the managerial implications that this study provide would discuss the idea of creating marketing campaigns to emphasize the difference between genuine and counterfeit products which will be aimed to spread slowly to the whole customer base. Additionally, cheaper genuine products may also be proposed to help combat counterfeit products within the aspect of status consumption. Consequently, customer attention would shift in the direction of being favorable of genuine products.